BRICS EXPANSION IN THE MIDDLE EAST FROM POLITICAL ECONOMY PERSPECTIVE - Yusuf Idrus Malik; Halilintar Yusuf Kohar; Herza Nabilah Zeth Tungkagi (CMES (Center of Middle Eastern Studies), 2024)
This article examines the expansion of the BRICS organization in the Middle East through the lens of the political economy. The BRICS countries, including Brazil, Russia, India, China, and South Africa, have expanded their presence in the Middle East. Despite extensive research on the BRICS studies, more comprehensive studies need to explore the analysis of BRICS expansion to the region. Utilizing a qualitative approach, this study conducts a literature review to explore the depth and breadth of its expansion. The findings of this research reveal some of the interests of the BRICS countries in securing energy resources, establishing political influence, and tapping into the region's economic potential. Furthermore, the BRICS countries see the Middle East as a crucial region for their geopolitical ambitions and an opportunity to challenge Western dominance in global politics and economics.